Corporate social performance and the attraction of future employees: The role of ethical reputation and moral identity - Silva, V. H.; Duarte, A.P.; Simões, E.; Neves, J. (VII Conference Research and Intervention in Human Resources, 2017)
Prior research suggests that corporate social performance of organizations influences their attractiveness as a future workplace (e.g., Duarte, Gomes & Neves, 2014; Greening & Turban, 2000). Ethical reputation, that reflects organizations’ commitment to ethics (Mulki & Jaramillo, 2011), is a construct positively related to corporate social responsibility (CSR) (Zhu, Sun, & Leung, 2014) which could be more or less salient according the centrality that moral values assume in individual identity (Aquino & Reed, 2002). The main goal of this research was to investigate the relationships among CSR, organizational attractiveness, ethical reputation and moral identity using a moderated mediation analysis. In this study CSR perception was manipulated in order to observe its effect on organizational attractiveness through the mediating effect of ethical reputation moderated by moral identity. Participants (N = 222; 60.2% females; M age = 26.7 years old) were randomized by two experimental conditions, responding to an electronic questionnaire containing the description of an organization that met (high involvement condition) or not (low involvement condition) a set of CSR practices, followed by questions about other variables of interest. The results of moderated mediation analysis using PROCESS (Hayes, 2013) show that CSR affects directly and indirectly, through ethical reputation, the evaluation of the organization as a future workplace and the power of this relationship depends on moral identity. In practical terms, this means that in the “war for talent” (Bhattacharya, Sen, & Korschun, 2008), organizations can make use of information about their corporate social performance and ethical reputation as a tool to attract potential candidates, alongside the traditional information on organizational attributes and job characteristics.